2011
DOI: 10.1111/j.1542-474x.2010.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Electrocardiographic Features and Mechanical Dyssynchrony in Heart Failure Patients with Left Bundle Branch Block

Abstract: The following electrocardiographic parameters were related to the degree of mechanical dyssynchrony: QRS duration and notches in QRS. In addition, the patients tend to have highest S amplitude in precordial leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
0
0
1
Order By: Relevance
“…The association between QRS duration and dyssynchrony has been reported repeatedly, although the association is still unclear especially in patients with CLBBB . Our study also revealed an association between QRS duration and dyssynchrony (OR 1.03, P = 0.032, Table ), strongly supporting the idea that t‐CLBBB criteria should include a wider QRS …”
Section: Discussionsupporting
confidence: 80%
“…The association between QRS duration and dyssynchrony has been reported repeatedly, although the association is still unclear especially in patients with CLBBB . Our study also revealed an association between QRS duration and dyssynchrony (OR 1.03, P = 0.032, Table ), strongly supporting the idea that t‐CLBBB criteria should include a wider QRS …”
Section: Discussionsupporting
confidence: 80%
“…Estudo brasileiro encontrou somente moderada correlação entre duração do QRS e dissincronia intra e interventricular 195 .…”
Section: Dispositivos Implantáveis Deunclassified